Ragam Bentuk dan Desain Sarana Penjahit Keliling di Wilayah Perumahan Bintaro Jaya Sektor 1 dan 2, Jakarta Selatan - Awang Eka Novia Rizali (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2016)
The national economic changes have effect the life of urban communities. The difficulties of meeting the needs of daily living  drive a person tofind a way to increase their income. Mobile tailor is a service to make and to repair the clothes, known also as "tukang permak Levis". Mobile tailors can be seen in Jakarta and suburban and approaching the customers in residence area. The means of mobile tailor is a modification of bicycle that has simple designed by the user. This research focus on theform and design varieties of mobile tailors in Bintaro Jaya Sektor 1 and 2 residence area, South Jakarta. The method is qualitative method with design approach. The interviewees of this research are tailors who have variousform and design of mobile tailors in the research area. The data collecting method is observation and interview with the interviewees. The result of this research is the description of mobile tailor'sform and design that has changing as the changing of the needs and condition of the user, and user convortability in doing the activities.Keywords: form, design, mobile, tailors, means